Peran Pemerintah Desa Dalam Pengembangan Desa Wisata di Kabupaten Mojokerto : Studi Pada Desa Wisata Kampung Majapahit Bejijong Kecamatan Trowulan Kabupaten Mojokerto - Febriani, Shelly Regeta; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tourism is a strategic sector in economic development because it drives growth, creates jobs, and empowers communities. The Mojokerto Regency Government is focusing on developing tourist villages, including the Kampung Majapahit Bejijong Tourist Village, which has cultural and historical potential as its main attractions. However, there are still challenges such as suboptimal management, internal conflicts, and insufficient facilities. Therefore, the active role of the village government is needed in the sustainable development of tourist villages. This study aims to identify and describe the role of the Bejijong Village Government in the development of the Kampung Majapahit Bejijong tourist village in Mojokerto Regency. The method used is qualitative descriptive with a case study approach, through observation, documentation, and interviews. The research location is in the Kampung Majapahit Bejijong Tourism Village. Data analysis was conducted using the interactive model of Miles and Huberman in Sugiyono (2022), namely data collection, data reduction, data presentation, and conclusion drawing. The role of the village government was analyzed using six indicators from Ife and Tesoriero (2005) in Susanti (2015): role in social animation, mediation and negotiation, support provider, group facilitation, utilization of resources and skills, and organization. The results show that the Bejijong Village Government plays an active role, particularly in mediation and support provision. However, challenges include low community participation, weaknesses in facilitation, and insufficient promotion and effective digitalization. In conclusion, the role of the village government is not yet fully optimal and equitable across all aspects, necessitating strengthened empowerment and sustainable strategies.